The crystal and solution structure of YdiE from Escherichia coli. Issue 7 (1st July 2015) - Nishimura, Kaoru; Addy, Christine; Shrestha, Rojan; Voet, Arnout R. D.; Zhang, Kam Y. J.; Ito, Yutaka; Tame, Jeremy R. H.
<x xml:space="preserve">Abstract</x> Iron‐containing porphyrins are essential for all life as electron carriers. Since iron is poorly available in an oxidizing environment, bacterial growth may be restricted by iron limitation, and this has led to the evolution of a huge variety of iron‐uptake systems. Among pathogens, iron scavenging from the haemoglobin of an animal host is a common means of acquiring sufficient iron for growth. The Isd system of Staphylococcus aureus is a well studied example; the bacterium devotes considerable resources to the construction of surface proteins that deftly remove haem from haemoglobin and pass it along a chain of related proteins, eventually delivering the haem to the cytoplasm, where it can be utilized or degraded. All organisms, however, must deal with haem and related molecules, which are by their nature hydrophobic and prone to precipitate, and which tend to promote the formation of reactive oxygen species. Chaperones are an obvious solution to the problem of maintaining a pool of haem for insertion into cytochromes without allowing naked haem to cause damage. YdiE is a very small protein from Escherichia coli of only 63 residues which may play a role in haem trafficking. Here, NMR analysis and the crystal structure of the protein to high resolution are reported.